California at war : the state and the people during World War I - North, Diane M. T. (University Press of Kansas, 2018)
"The United States' participation in World War I changed the daily lives of Californians. They served in the military, volunteered with overseas aid organizations, and raised millions to help war refugees and fund the war effort. The federal government expanded military bases and training camps in California, businessmen secured military contracts, and university scientists conducted war-related research. Wartime California was also a place of suspicion, censorship, illegal evidence gathering, and intrusive domestic surveillance, where citizens rejected progressivism in favor of anti-civil liberties measures and where fear of radicals, dissenters, and Asian Americans rose. In California at War, Diane North focuses on people and tells their stories, using the Golden State as a lens through which to see a bigger picture. As reader and World War I expert Steve Trout said in his report on the manuscript: "Bringing the history of American participation in the Great War down to the state level--in a work this well-written and deeply researched--produced what was, for me at least, a surprising effect: I felt the weight of those nineteen transformative months in 1917-1918 as never before."--Provided by publisher